2004
DOI: 10.2174/1389450043345263
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytochrome P450 Enzymes in the Metabolism of Risperidone and Its Clinical Relevance for Drug Interactions

Abstract: In the recent years it has been increasingly recognized that pharmacogenetical factors play an important role in the drug treatment. These factors may influence the appearance of side-effects and drug interactions due to interindividual differences in the activity of metabolizing enzymes. Risperidone in humans is mainly metabolized to 9-hydroxyrisperidone by the polymorphic cytochrome enzyme P450 2D6 (CYP2D6). Plasma concentrations of risperidone and 9-hydroxyrisperidone show large interindividual variability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 0 publications
2
39
0
2
Order By: Relevance
“…In accord with this finding CYP2D6 PM subjects had an increased ratio of risperidone to 9-hydroxyrisperidone but no overall difference in the concentration of the active moiety (Olesen et al 1998). However, possibly as a result of the pharmacological activity of 9-hydroxyrisperidone, the significance of the CYP2D6 phenotype for the safety and efficacy of the drug remains unclear (Scordo et al 1999;Berecz et al 2004).…”
Section: Risperidonementioning
confidence: 70%
See 1 more Smart Citation
“…In accord with this finding CYP2D6 PM subjects had an increased ratio of risperidone to 9-hydroxyrisperidone but no overall difference in the concentration of the active moiety (Olesen et al 1998). However, possibly as a result of the pharmacological activity of 9-hydroxyrisperidone, the significance of the CYP2D6 phenotype for the safety and efficacy of the drug remains unclear (Scordo et al 1999;Berecz et al 2004).…”
Section: Risperidonementioning
confidence: 70%
“…The debrisoquine metabolic ratio (an in-vivo marker of CYP2D6 activity) and the number of active CYP2D6 genes have been related to steady-state plasma concentrations of risperidone in patients (Berecz et al 2004). Recently, a large study of 136 schizophrenic patients who received risperidone was concluded (Kakihara et al 2005).…”
Section: Risperidonementioning
confidence: 99%
“…Bireyler arası dozlardaki farklılıklar ilaç yan etkisiyle ilişkili olabilir. Ek olarak CYP2D6 genetik polimorfizmi ve plazma risperidon ve hidroksirisperidon düzeylerinin değerlendirilmesi yan etki potansiyelini azaltabilir 5,12 . Risperidonun kesilmesiyle vakanın mevcut şikayetlerini yatıştırmaya yönelik parenteral haloperidol tedavisi ve lorazepam tedavisi başlandı.…”
Section: Discussionunclassified
“…45 Risperidone is metabolized and can contribute to numerous drug interactions because it is metabolized by CYP3A4, the most common drug-metabolizing enzyme. 46 Many children have GI problems 47 and are given numerous medications that change the GI flora. In particular, they are often given antifungal medications, 16,17 such as fluconazole, which is a CYP3A inhibitor and can affect the metabolism of many drugs (Fig.…”
Section: Metabolismmentioning
confidence: 99%